Fluorescence-Activated Cell Sorting as a Method to Isolate Ionocyte Populations from Gill Tissue - El-Sakhli, Ibragim (Université d'Ottawa / University of Ottawa, 2018)
In freshwater fish, such as the rainbow trout (Oncorhynchus mykiss), higher ion concentrations in the body fluids relative to the dilute surrounding environment lead to diffusive ion loss that is countered by active ion uptake. Active ion uptake is achieved via specialised cells in the gill epithelium known as ionocytes, with the species studied to date exhibiting multiple ionocyte subtypes with specific complements of ion transport proteins. To better understand the functions and responses of each ionocyte subtype, methods are needed to isolate specific ionocyte subtypes. This thesis developed a method to use fluorescence-activated cell sorting (FACS) to isolate the peanut lectin agglutinin-positive (PNA+) ionocyte subtype of the trout gill, which is posited to be a base-secreting cell that takes up Cl- ions. A suspension of gill cells dissociated using ethylenediaminetetraacetic acid (EDTA) was labelled with biotinylated PNA that was detected using streptavidin conjugated to a fluorophore, and subjected to FACS to yield a population of PNA+ ionocytes of high viability and purity. To validate the utility of the approach, it was used in a proof-of-principle experiment to evaluate transcript abundance of cytosolic carbonic anhydrase (CAc) in PNA+ ionocytes in trout that were subjected to metabolic alkalosis. This experiment revealed that the relative transcript abundance of CAc was significantly elevated in PNA+ ionocytes of alkalotic trout relative to that of control trout (P = 0.001; N = 7), a response that is consistent with the expected role of PNA+ ionocytes in compensation for systemic alkalosis.
Keywords: FACS; Rainbow trout; Fluorescence-activated cell sorting; Ionocyte